Strategi Pengelolaan Sektor Pariwisata oleh Pokdarwis Desa Wisata Srikeminut pada Masa Krisis Pandemi COVID-19 - Dewi, Vivian Noor Safira (Gadjah Mada Journal of Tourism Studies, 2023)
Srikeminut Tourist Village is among the tourist communities adversely affected by the COVID-19 pandemic. Pokdarwis is among the entities tasked with managing the tourism industry during the pandemic. By applying the theory of tourism disaster crisis management offered by Ritchie (2004), this research endeavors to ascertain the approach adopted by the Pokdarwis of Srikeminut Tourism Village in handling the tourism industry amidst the Covid-19 pandemic crisis that transpired between 2020 and 2022. Therefore, this research focuses on two primary topics: firstly, the categorization of the Pokdarwis strategy about the stages of crisis management, and secondly, the identification of the Pokdarwis strategy in the recovery of the tourism sector. The findings indicated that Pokdarwis resorted to a sequence of strategic implementations in light of the pandemic rather than engaging in preventative measures and strategic planning. Implementing health protocols, creating virtual events, limiting the number of visits, collaborating with internal and external parties, suspending several tourist activities, and promoting tourist attractions via Instagram are all methods to achieve this objective. Pokdarwis' approach to tourism sector management has facilitated the gradual recovery of Srikeminut Tourist Village from the pandemic crisis. By 2022, it will be possible to classify the Srikeminut Tourist Village as having reached a stage in its crisis anatomy known as the long term (recovery), wherein all forms of tourism activities can be resumed as before, and the village community will have acclimated to the new normalcy. To attain this position, Pokdarwis engaged in a succession of partnerships with internal and external entities, implemented a crisis communication strategy, and provided tourism managers and Pokdarwis personnel with a variety of training on sector management.